Paradigm of Pancasila Economic as The Identity of Indonesia Nation - Rizal Al Hamid (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Among the solutions in dealing with the problems of this country is to regenerate the spirit of Pancasila. It is the source of the Indonesian entity as a State. Pancasila also has a function as an ideology, principles and philosophy of the nation, as well as a basic principal representation for an independent country. Therefore, the revitalization of Pancasila should be the main objective of a series of government discourses, so that the values contained in it are able to permeate every society of this country. The Founding Fathers believed that Pancasila was not only able to unite the citizen, but also to alleviate them from the shackles of social inequality, poverty, hunger, and rampant corrupt practices. In this paper, we describe a series of discourses about the economy that is unique to this country, namely the Pancasila Economy. It is believed to be able to free the shackles of these downturns, even without harming other parties, as happened in the economic concept of capitalist, socialist, and liberal. The findings of this paper are that in fact, Pancasila Economy is part of the heterodox economic approach, which contains the concept of a socialist and capitalist economy. Even so, Pancasila Economics does not mean adopting the two economic concepts, but rather a hybrid form and has been modified in line with the values contained in the principles of Pancasila.